Systematic review of yoga for symptom management during conventional treatment of breast cancer patients. (August 2022) - Selvan, Pooja; Hriso, Chloe; Mitchell, Julita; Newberg, Andrew
Abstract: Introduction: Breast cancer is one of the most commonly diagnosed cancers in women in the US, and its treatments have significant physical and psychological side effects and long-term complications causing significant morbidity and decreased quality of life. Integrative medicine modalities, such as Yoga, have been found to reduce side effects of conventional treatments without interfering with the treatment itself and improve quality of life. In this systematic review, we specifically explored Yoga as a potential option for symptomatic management in patients undergoing conventional breast cancer treatments. Methods: We performed a literature search that was conducted to include the databases PubMed, PsychINFO, Cochrane Library, Scopus, and CINAHL, resulting in 28 randomized controlled trial (RCT) articles. We review the results of these trials regarding the impact of Yoga in this patient population. Results: Overall, the majority of the RCT articles showed significant benefits of Yoga intervention in various aspects of quality of life, fatigue, nausea/vomiting, sleep quality, anxiety, depression, and distress. There are several studies that have explored the physiological mechanism behind the effects of Yoga and found that Yoga affects both the immune response and inflammation. Discussion: These studies revealed that Yoga has a potential therapeutic role in the symptomatic management of breast cancer patients, enhancing quality of life during treatment as well as improving adherence to treatment. Future studies with more defined and consistent methodologies are necessary to fully understand the potential use of Yoga therapy in patients with breast cancer. Highlights: Yoga interventions in patients with breast cancer show significant benefits in various aspects of quality of life. Yoga interventions also appear to improve anxiety, depression, and distress in patients with breast cancer. The effects of Yoga interventions appear to be associated with changes in brain function. Future studies with better methodologies are necessary to fully understand the potential use of Yoga in patients with breast cancer.